2002
DOI: 10.1002/1521-4028(200210)42:5<311::aid-jobm311>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorine, biodegradable dissolved organic carbon and suspended bacteria on biofilm development in drinking water systems

Abstract: The influence of chlorine levels, the concentration of dissolved organic carbon and the abundance of bacteria in suspension, on the formation of biofilms on experimental glass surfaces were evaluated. Twelve reactors, packed with glass spheres, were continuously perfused with tap water. The properties of water were altered in different ways: chlorine was neutralized by the addition of thiosulfate, the levels of assimilable organic carbon were increased through the addition of acetate, and the bacterial load wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…In Figure 1a-c, the curves representing the numbers of cells in the biofilm (total cells, total L. pneumophila and HPC, respectively) follow the traditional shape for biofilm accumulation (Rogers et al 1994a,b;Codony et al 2002). Most of the total cells and total L. pneumophila (calculated using the L. pneumophila specific PNA probe) attached during the first few days and then fluctuated within a narrow range (p 4 0.05).…”
Section: Pneumophila In Heterotrophic Biofilmssupporting
confidence: 66%
See 1 more Smart Citation
“…In Figure 1a-c, the curves representing the numbers of cells in the biofilm (total cells, total L. pneumophila and HPC, respectively) follow the traditional shape for biofilm accumulation (Rogers et al 1994a,b;Codony et al 2002). Most of the total cells and total L. pneumophila (calculated using the L. pneumophila specific PNA probe) attached during the first few days and then fluctuated within a narrow range (p 4 0.05).…”
Section: Pneumophila In Heterotrophic Biofilmssupporting
confidence: 66%
“…This result is supported by two studies conducted by Codony et al (2002Codony et al ( , 2005, who showed that the total number of cells were similar in the control and chlorinated conditions, but treated cells were less cultivable. In the present work, HPC numbers in the control were 2-log lower than in biofilms formed in chlorinated water, although the difference between the two concentrations used was not significant (p 4 0.05).…”
Section: Pneumophila In Heterotrophic Biofilmsmentioning
confidence: 72%
“…In fact, the HPC numbers for the chlorinated biofilms were almost 3 log lower than that of the control. These results are supported by two studies conducted by Codony et al (7,8), where it was shown that under chlorinated conditions, the total number of cells was similar to that seen in the control study but that the cells were less culturable.…”
supporting
confidence: 70%
“…As observed for planktonic samples, no cultivable H. pylori was recovered on HP on May 9, 2018 by guest http://aem.asm.org/ medium for any of the biofilm samples. The biofilm development followed kinetics described by other authors; adhesion of most cells took place on the first day, but no statistically significant change occurred after this (P Ͼ 0.05) (13,32). It should be noted that this pseudo-steady state is actually the result of a dynamic equilibrium typical of biofilms, where parts of biofilms detaching from coupons are balanced by the adherence of new cells (35,39).…”
Section: Resultsmentioning
confidence: 99%